2008
DOI: 10.3892/or.19.1.111
|View full text |Cite
|
Sign up to set email alerts
|

Expression of hypoxia inducible factor-1α (HIF-1α) and glucose transporter-1 (GLUT-1) in ovarian adenocarcinomas: Difference in hypoxic status depending on histological character

Abstract: Abstract. The expression of hypoxia inducible factor-1α (HIF-1α) and glucose transporter-1 (GLUT-1) was immunohistochemically analyzed in ovarian adenocarcinomas with the aim of elucidating whether hypoxic status is associated with histological type or structural character. The following ovarian adenocarcinomas were used: serous adenocarcinoma (SEA), 21 cases; mucinous adenocarcinoma (MUA), 19 cases; endometrioid adenocarcinoma (ENA), 16 cases; clear cell adenocarcinoma (CLA), 19 cases. High-level expression (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 15 publications
1
45
0
Order By: Relevance
“…Hypoxia-inducible factor-1α (HIF-1α), a transcription factor associated with the cellular response to hypoxia (12), upregulates the expression of several hypoxia response genes, including GLUT-1 (1). The overexpression of GLUT-1 increases glucose transport to meet the energy requirements of malignant tumour cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxia-inducible factor-1α (HIF-1α), a transcription factor associated with the cellular response to hypoxia (12), upregulates the expression of several hypoxia response genes, including GLUT-1 (1). The overexpression of GLUT-1 increases glucose transport to meet the energy requirements of malignant tumour cells.…”
Section: Introductionmentioning
confidence: 99%
“…Malignant tumours are considered to be in a hypoxic state (1). Under hypoxic conditions, cancer cells switch from oxygen-dependent glucose metabolism to oxygen-independent glycolysis (2).…”
Section: Introductionmentioning
confidence: 99%
“…15 HIF-1alpha is activated by hypoxia involving the PI-3K/AKT/mTOR signaling pathway. Glut-1 expression has been correlated with malignant transformation, histological characteristics, 8 and tumor angiogenesis. 16 Because it promotes malignant transformation and development of histological tumor characteristics 7 including angiogenesis, 16 inhibition of Glut-1 is currently being evaluated as a therapeutic strategy.…”
Section: Recently Kurman Et Al Proposed a New Classification Ofmentioning
confidence: 99%
“…7 Glut-1 is a glucose transporter-1 molecule essential for tumor cells to survive, especially in a severely hypoxic microenvironment. 8 iNOS synthesizes nitric oxide (NO), which causes NO-mediated apoptosis in the presence of inflammatory mediators like bacterial endotoxins. 9 Cyclooxygenase enzyme (COX) is a key regulatory enzyme in the prostaglandin/eicosanoid synthetic pathway.…”
mentioning
confidence: 99%
“…Glut-1 is a prototype of the Glut family and is widely distributed in normal tissues including RBCs [25]. Studies on ovarian cancer have suggested that Glut-1 is overexpressed and correlated with tumor aggressiveness and poor prognosis [15,26].…”
Section: Discussion:-mentioning
confidence: 99%